Influence of moist air in copper heat sinks: Analysis through the entropy generation minimization criterion (2015)
Many factors affect heat transfer during the cooling of modern electronic devices. Today, knowledge accrues from modeling, simu-lation, and experimentation. This allows predicting and calculating features of heat transfer phenomena, to some extent. Examples include the amount of heat generated and removed, the required physical properties of the working fluid, and the required material properties of the heat sink, among other parameters. This article describes some simulation results of using air with a given relative humidity (10 %, 50 % and 90 %). Its influence on the heat transfer process was also analyzed. Results show a measurable effect of using humidified air instead of dry air and copper as a bulk material. The heat transfer rate increased about 20 % when using air with 90 % relative humidity passing through a rectangular microchannel heat sink made of copper.